Descriptive characteristics of colon and rectal cancer recurrence in a Danish population-based study. (3rd August 2017) - Holmes, Ashley C.; Riis, Anders H.; Erichsen, Rune; Fedirko, Veronika; Ostenfeld, Eva Bjerre; Vyberg, Mogens; Thorlacius-Ussing, Ole; Lash, Timothy L.
Abstract: Background: Recurrence is a common outcome among patients that have undergone an intended curative resection for colorectal cancer. However, data on factors that influence colorectal cancer recurrence are sparse. We report descriptive characteristics of both colon and rectal cancer recurrence in an unselected population. Material and methods: We identified 21, 152 patients with colorectal cancer diagnosed between May 2001 and December 2011 and registered with the Danish Colorectal Cancer Group. Recurrences were identified in 3198 colon and 1838 rectal cancer patients during follow-up. We calculated the frequency, proportion, and incidence rates of colon and rectal cancer recurrence within descriptive categories, and the cumulative five- and ten-year incidences of recurrence, treating death as a competing risk. We used a Cox proportional hazard model to calculate hazard ratios (HR) and 95% confidence intervals (CI). Results: Recurrence risk was highest in the first three years of follow-up. Patients <55 years old at initial diagnosis (incidence rate for colon: 7.2 per 100 person-years; 95% CI: 6.5–7.9; rectum: 8.1 per 100 person-years; 95% CI: 7.2–9.0) and patients diagnosed with stage III cancer (colon HR: 5.70; 95% CI: 4.61–7.06; rectal HR: 7.02; 95% CI: 5.58–8.82) had increased risk of recurrence. Patients diagnosed with stage III cancer from 2009 to 2011 had a lower incidence of recurrence than those diagnosed with stage III cancer in the years before. Cumulative incidences of colon and rectal cancer recurrence were similar for both cancer types among each descriptive category. Conclusions: In this population, increases in colorectal cancer recurrence risk were associated with younger age and increasing stage at diagnosis. Cumulative incidence of recurrence did not differ by cancer type. Descriptive characteristics of colon and rectal cancer recurrence may help to inform patient–physician decision-making, and could be used to determine adjuvant therapies or tailor surveillance strategies so that recurrence may be identified early, particularly within the first 3 years of follow-up.